Sistem Pendukung Keputusan Penerima Pembiayaan Akad Qordh Menggunakan Metode Analytical Hierarchy Process dan Weighted Product - Restu Nur Hakim; Muhammad Hamka (Universitas Muhammadiyah Purwokerto, 2021)
Islamic financial services unit is a business unit in a cooperative whose business activities are engaged in financing, investment and savings in accordance with the profit sharing pattern (sharia). This study aims to create a Decision Support System to determine the acceptance of qordh contract financing using the Analitycal Hierarchy Process (AHP) method used to determine the criteria weights and the Weighted Product (WP) method is used to determine the qordh contract financing recipient ranking. Obtained the results of the AHP method calculation with the highest priority, namely the guarantee criteria with a value of 39%, the criteria for work with a value of 24%, the criteria for the amount of financing with a value of 9%, the term criteria with a value of 9%, the age criteria with a value of 14%, and the last criteria financing history with a priority value of 4%.Based on the WP calculation results, the first recommended alternative results obtained qordh contract financing is alternative 7 with a V_7 value of 0.159, followed by alternative 3 with a V_3 value of 0.109, alternative 1 with a V_1 value of 0.105, alternative 6 with a V_6 value of 0.098, alternative 8 with a V_8 value of 0.096, alternative 9 with a V_9 value of 0.093, alternative 4 with a V_4 value of 0.082, alternative 5 with a V_5 value of 0.081, alternative 2 with a V_2 value of 0.061, alternative 10 with a V_10 value of 0.057, and the The last is alternative 11 with a value of V_11 which is 0.056.